AA-amyloidosis in captive northern tree shrews (Tupaia belangeri). Issue 2 (March 2022) - Klein, Annette; Radespiel, Ute; Felmy, Felix; Brezina, Tina; Ciurkiewicz, Malgorzata; Schmitz, Jessica; Bräsen, Jan Hinrich; Linke, Reinhold Paul; Reinartz, Sina; Distl, Ottmar; Beineke, Andreas
A high prevalence of AA-amyloidosis was identified in a breeding colony of northern tree shrews ( Tupaia belangeri ) in a retrospective analysis, with amyloid deposits in different organs being found in 26/36 individuals (72%). Amyloid deposits, confirmed by Congo red staining, were detected in kidneys, intestines, skin, and lymph nodes, characteristic of systemic amyloidosis. Immunohistochemically, the deposited amyloid was intensely positive with anti-AA-antibody (clone mc4), suggesting AA-amyloidosis. The kidneys were predominantly affected (80%), where amyloid deposits ranged from mild to severe and was predominantly located in the renal medulla. In addition, many kidneys contained numerous cysts with atrophy of the renal parenchyma. There was no significant association between concurrent neoplastic or inflammatory processes and amyloidosis. The lack of distinctive predisposing factors suggests a general susceptibility of captive T. belangeri to develop amyloidosis. Clinical and laboratory findings of a female individual with pronounced kidney alterations were indicative of renal failure. The observed tissue tropism with pronounced kidney alterations, corresponding renal dysfunction, and an overall high prevalence suggests amyloidosis as an important disease in captive tree shrews.